2007
DOI: 10.2478/v10006-007-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

A Backstepping Approach to Ship Course Control

Abstract: As an object of course control, the ship is characterised by a nonlinear function describing static manoeuvring characteristics that reflect the steady-state relation between the rudder deflection and the rate of turn of the hull. One of the methods which can be used for designing a nonlinear ship course controller is the backstepping method. It is used here for designing two configurations of nonlinear controllers, which are then applied to ship course control. The parameters of the obtained nonlinear control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 24 publications
1
69
0
Order By: Relevance
“…Our results are a continuation of studies initiated earlier (Witkowska et al, 2007;Witkowska and Smierzchalski, 2009).…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our results are a continuation of studies initiated earlier (Witkowska et al, 2007;Witkowska and Smierzchalski, 2009).…”
Section: Introductionsupporting
confidence: 72%
“…Genetic operations comprised classical selection, crossover and mutation. For more information about genetic operations, see the work of Witkowska et al (2007).…”
Section: Optimization Processmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for certain faults, this controller cannot provide sufficiently good control. The nonlinear backstepping technique applied into the offshore vessel is found in the work of Witkowska et al (2007), and further research about sliding mode control on marine vessels is found in that by Tomera (2010).…”
Section: Fault Tolerant Controlmentioning
confidence: 99%